Multi-year field evaluation of nicotianamine biofortified bread wheat - Beasley, Jesse T.; Bonneau, Julien P.; Moreno-Moyano, Laura T.; Callahan, Damien L.; Howell, Kate S.; Tako, Elad; Taylor, Julian; Glahn, Raymond P.; Appels, Rudi; Johnson, Alexander A. T. (Wiley, 2022)
Conventional breeding efforts for iron (Fe) and zinc (Zn) biofortification of bread wheat (Triticum aestivum L.) have been hindered by a lack of genetic variation for these traits and a negative correlation between grain Fe and Zn concentrations and yield. We have employed genetic engineering to constitutively express (CE) the rice (Oryza sativa) nicotianamine synthase 2 (OsNAS2) gene and upregulate biosynthesis of two metal chelators – nicotianamine (NA) and 2′-deoxymugineic acid (DMA) – in bread wheat, resulting in increased Fe and Zn concentrations in wholemeal and white flour. Here we describe multi-location confined field trial (CFT) evaluation of a low-copy transgenic CE-OsNAS2 wheat event (CE-1) over 3 years and demonstrate higher concentrations of NA, DMA, Fe, and Zn in CE-1 wholemeal flour, white flour, and white bread and higher Fe bioavailability in CE-1 white flour relative to a null segregant (NS) control. Multi-environment models of agronomic and grain nutrition traits revealed a negative correlation between grain yield and grain Fe, Zn, and total protein concentrations, yet no correlation between grain yield and grain NA and DMA concentrations. White flour Fe bioavailability was positively correlated with white flour NA concentration, suggesting that NA-chelated Fe should be targeted in wheat Fe biofortification efforts.